Representation Of Women In The Writing And Pictures Of The Back Of The Truck: An Analysis Of Sexist Language - Nurul Hidayah, Ditya; Ramadhan, Amalia; Nuruzzaman; Dian Lestari, Aghnia (ann4publisher@gmail.com, 2024)
Communication media has an essential role in shaping public perception of women. However, the representation of women in the media often has a negative impact. For example, the writing and pictures behind the truck often contain messages that demean women through objectifying diction and visuals. This study aims to analyze the representation of women in truck visual media and shows that the media reinforces gender stereotypes and limits women's potential in society. A qualitative research approach is applied to explore natural phenomena through triangulation techniques and inductive and descriptive data analysis. Identifying key informants is crucial in this method, with selection based on their level of involvement in the social situation being studied. The researcher conducted direct interviews with five informants who have relevant knowledge and experience, using the Critical Discourse Analysis theory that underlies this study to explore how women are represented in the tailgate of trucks in the form of writing and drawings. The findings of this study reveal that the sexist language in the tailgate of a car reflects the view that women are (1) sexual objects, (2) inanimate objects, (3) vulnerable figures who need sexual attention, and (4) weak figures. The representation of women in the writings and images on the back of the truck not only strengthens the patriarchal power structure in Indonesian society but also highlights the complexity of the interaction between language, culture, and power.